AMG853, A Bispecific Prostaglandin D2 Receptor 1 and 2 Antagonist, Dampens Basophil Activation and Related Lupus-Like Nephritis Activity in Lyn-Deficient Mice - Pellefigues, Christophe; Tchen, John; Saji, Chaimae; Lamri, Yasmine; Charles, Nicolas (Frontiers in Immunology, 2022)
Systemic lupus erythematosus is a complex autoimmune disease during which patients develop autoantibodies raised against nuclear antigens. During the course of the disease, by accumulating in secondary lymphoid organs (SLO), basophils support autoreactive plasma cells to amplify autoantibody production. We recently showed that murine lupus-like disease could be controlled by 10 days of oral treatment with a combination of prostaglandin D2 (PGD2) receptors (PTGDR) antagonists through inhibition of basophil activation and recruitment to secondary lymphoid organs (SLO). Importantly, inhibiting solely PTGDR-1 or PTGDR-2 was ineffective and lupus-like disease development could only be dampened by using antagonists for both PTGDR-1 and PTGDR-2. Here, we aimed at establishing the proof of concept that a clinically relevant bispecific antagonist of PTGDR-1 and -2 could be efficient to treat murine lupus-like nephritis. Sick Lyn deficient female mice were treated with AMG853 (vidupiprant, a bispecific PTGDR-1/-2 antagonist) for 10 days. This led to dampening basophil activation and recruitment in SLO and was associated with a decrease in plasmablast expansion and IgE production. 10 days of treatment with AMG853 was consequently sufficient to reduce dsDNA-specific IgG titers, circulating immune complex glomerular deposition and renal inflammation, hallmarks of lupus-like disease. Thus, bispecific PTGDR-1 and PTGDR-2 antagonists, such as AMG853, are a promising class of drugs to treat or prevent organ damages in systemic lupus erythematosus.